A Dialogue Between Computational Thinking And Interdisciplinarity Using Scratch Software - Zampieri, Maria Teresa; Javaroni, Sueli Liberatti [UNESP] (Univ Antioquia,grupo Chhes, 2020)
In this paper, the purpose is to discuss results of a continuing education action with teachers, linked to the university extension project Computational Thinking and Interdisciplinarity in the classroom, developed within the Postgraduate Program in Mathematics Education at Sao Paulo State University (UNESP), Rio Claro (Sao Paulo), Brazil. The development of interdisciplinary activities by teachers using Scratch software is highlighted, pointing out how this is reflected in the classroom, from the development of an interdisciplinary activity in two classes taught by the teacher of Geography, a participant of this formative action. The qualitative approach was adopted, and the methodological procedures used were video recording of the meetings, writing of field diaries, prepared by all the involved proposers, and recording of all the developed activities. Data analysis highlights how important this partnership between university and school was because it contributed to transform the knowledge of teachers, researchers, and students through the development of Computational Thinking.
Keywords: University-school Partnership; Scratch; Interdisciplinary Activities; Mathematics Education